Composite coating material for repairing corroded surface of inner diameter of hydraulic cylinder body and preparation method of composite coating material

By modifying the epoxy resin composite coating material, using layer-by-layer self-assembly technology and nitrogen-doped carbon quantum dots, the problem of corrosion of the inner diameter of the hydraulic cylinder is solved, efficient and reliable repair effect is achieved, and the use of the hydraulic system is improved life.

CN119505639AActive Publication Date: 2025-02-25NANJING UNIV OF AERONAUTICS & ASTRONAUTICS +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411687243.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Corrosion of the inner diameter of the hydraulic cylinder leads to rough surface of the cylinder inner diameter, changes in morphology, and severe wear of the sealing ring, affecting the sealing properties and service life. The existing repair technology has problems such as thermal stress, large deformation, high cost, and long treatment cycle.

Method used

Using modified epoxy resin composite coating materials, the corrosion inhibitor materials are adsorbed through layer-by-layer self-assembly technology to prepare porous polyether etherketone nanoparticles loaded with corrosion inhibitors, combined with nitrogen-doped carbon quantum dots to form high-performance coatings Layer material used to repair the corrosive surface of the inner diameter of the hydraulic cylinder.

Benefits of technology

It achieves the advantages of not introducing thermal stress, high repair efficiency and good accessibility, significantly improves the comprehensive performance of the coating, effectively suppresses corrosion of the inner diameter of the cylinder, and extends the service life of the hydraulic system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505639A_ABST
    Figure CN119505639A_ABST
Patent Text Reader

Abstract

The invention discloses a composite coating material for repairing the inner diameter corrosion surface of a hydraulic cylinder and a preparation method of the composite coating material, belongs to the field of metal anti-corrosion coatings, can effectively solve the problems that the inner diameter of the hydraulic cylinder is corroded, a matched sealing ring is seriously abraded and the like, and has the advantages that thermal stress is not introduced, the repairing efficiency is high and the accessibility is good. A corrosion inhibitor is stably combined on the surface of a porous polyether-ether-ketone nano-particle material by adopting a layer-by-layer self-assembly method to obtain polyether-ether-ketone nano-particles loaded with the corrosion inhibitor, and then the polyether-ether-ketone nano-particles loaded with the corrosion inhibitor are mixed with epoxy resin to obtain a uniform and stable modified epoxy resin anticorrosive coating. The obtained modified epoxy resin coating has excellent mechanical performance, corrosion resistance and machinability, can effectively inhibit the corrosion of the inner diameter of the cylinder body, maintains the dimensional precision and surface quality of the inner diameter of the cylinder body through machining, meets the service requirements of cylinder body parts, is simple and rapid in repairing process, can effectively repair damage caused by corrosion, and has a good application prospect. And the maintenance time and cost are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal anti-corrosion coatings, and in particular relates to a composite coating material for repairing inner diameter corroded surfaces of hydraulic cylinder bodies and a preparation method thereof. Background Art

[0002] In the fields of aerospace, automotive industry, etc., corrosion of the inner diameter of the hydraulic cylinder body is a common problem in the hydraulic system. It may occur due to medium corrosion, friction and wear, etc. This kind of corrosion will lead to increased surface roughness of the inner diameter of the cylinder body, changes in surface morphology and size, and even local wear or cracks. In addition, the morphological changes caused by corrosion will aggravate the friction and wear on the surface of the matching sealing ring, resulting in a significant reduction in its life, affecting the sealing and service life of the parts.

[0003] During routine inspection and maintenance, it is necessary to promptly replace the damaged seal ring in the hydraulic cylinder body and remove rust from the corroded surface. If the corrosion damage is not repaired and checked in time, it will cause hydraulic oil leakage and oil pressure drop, aggravate the hysteresis effect of the hydraulic cylinder's retraction and extension movement, and in severe cases, cause the hydraulic control system to fail, resulting in major safety accidents.

[0004] At present, traditional repair methods can be divided into hot repair and cold repair technology. Common hot repair technologies mainly include laser cladding, flame spraying, etc. The traditional hot repair temperature is higher than the eutectoid transformation temperature of steel, and there are problems such as large heat-affected area and severe deformation, which are difficult to meet the high-precision and high-performance requirements of hydraulic cylinders; while cold repair technology, such as micro-pulse cold welding or brush plating, has high repair costs and long processing cycles. In addition, the inner diameter seal size of the cylinder body is small, and the repair accessibility is poor. Conventional repair technology is difficult to act directly on the damaged surface. If new parts are replaced, there are problems of high update costs and difficult procurement. Therefore, it is of great significance to develop a composite coating repair technology for the inner diameter corrosion surface of the cylinder body.

[0005] At present, epoxy resin coating is commonly used to protect metal substrates. The chemical bonds such as ether or ester bonds contained in the epoxy resin molecular chain have good stability and are not easily corroded by common chemical corrosive media, and have a certain corrosion resistance. At the same time, due to the resistance effect of the film-forming material and the high density and sealing of the material itself, it can effectively block the erosion of external corrosive media and prevent corrosive substances from penetrating into the material. The high dielectric constant can effectively prevent the formation of corrosion circuits and play a role in shielding corrosive media. However, for different working conditions, the performance requirements of the corresponding coatings are also very different, so a single system of coatings is difficult to meet the requirements of different application environments. Summary of the invention

[0006] The present invention provides a composite coating material for repairing the inner diameter corroded surface of a hydraulic cylinder body and a preparation method thereof. The composite coating material is used to repair the corroded surface, which can make up for the shortcomings of a single system coating, improve the comprehensive performance of the coating, and effectively solve the problems of inner diameter corrosion of the hydraulic cylinder body and severe wear of the matching sealing ring. It has the advantages of not introducing thermal stress, high repair efficiency, and good accessibility.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions: A composite coating material for repairing the inner diameter corroded surface of a hydraulic cylinder body, wherein the material is a modified epoxy resin, wherein porous polyetheretherketone nanoparticles are uniformly mixed in the modified epoxy resin, and the surface of the porous polyetheretherketone is coated with a corrosion inhibitor.

[0008] The method for preparing the composite coating material comprises the following steps: 1) Mixing porous polyetheretherketone nanoparticles with a particle size of 150 to 200 nm with deionized water at a weight ratio of 1:15 to 1:20, and mixing evenly after heat preservation in a water bath to obtain a nano-polyetheretherketone dispersion; 2) Take the nano-polyetheretherketone dispersion and the positively charged polycation electrolyte solution with a concentration of 5 mg / mL and mix them evenly. After centrifugation, pour off the upper solution and wash the lower precipitate with deionized water; 3) The precipitate washed in step 2) was uniformly mixed with a negatively charged polyanion electrolyte solution with a concentration of 5 mg / mL, and the upper solution was discarded after centrifugation, and the lower precipitate was washed with deionized water; 4) The precipitate after washing in step 3) was mixed evenly with a 5 mg / mL nitrogen-doped carbon quantum dot (N-CQDs) corrosion inhibitor solution, centrifuged and discarded the upper solution, and the lower precipitate was washed with deionized water; 5) Repeat the above steps 3) and 4), put the final particles into an oven for drying, and obtain porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitor; 6) Mix the epoxy resin and diluent in proportion and stir under vacuum for 5 to 10 minutes; 8) adding porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitor to the diluted epoxy resin paste material, ultrasonically treating for 1 hour, and then stirring at a stirring speed of 280 r / min for 30 minutes in a vacuum environment; 9) After stirring is completed, add the curing agent after the modified material has cooled, and stir at room temperature for 15 minutes until the coating is evenly mixed and the color is brown-red, thereby obtaining a modified epoxy resin coating material.

[0009] In the above steps, the curing agent is an aromatic modified amine, and the volume usage is the same as that of the epoxy resin material; the positively charged polycationic electrolyte is polyethyleneimine, and the negatively charged polyanionic electrolyte is sodium polystyrene sulfonate; Repeat steps 3) and 4) to self-assemble positively charged polyethyleneimine and negatively charged polystyrene sulfonic acid polyelectrolyte multilayer films on the surface of porous polyetheretherketone nanoparticles, and adsorb nitrogen-doped carbon quantum dots corrosion inhibitors between polymer films to obtain polyetheretherketone nanoparticles coated with nitrogen-doped carbon quantum dots, sodium polystyrene sulfonate, nitrogen-doped carbon quantum dots, sodium polystyrene sulfonate, and polyethyleneimine in order: PEEK / PEI / PSS / N-CQDs / PSS / N-CQDs, to obtain porous polyetheretherketone nanoparticles loaded with corrosion inhibitors, and the number of repetitions usually depends on the performance requirements of the target; The polyetheretherketone is a polymer consisting of repeating units containing one ketone bond and two ether bonds in the main chain structure; The diluent is prepared from cyclohexanone, butyl acetate and anhydrous xylene in a volume ratio of 3:4:3. The volume ratio of the diluent is usually between 5% and 15%, which can adjust the viscosity of the epoxy resin material, improve the rheological properties, and make subsequent mixing more uniform.

[0010] The mass of the porous polyetheretherketone particles does not exceed 5% of the epoxy resin material.

[0011] Beneficial effects: The present invention provides a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body and a preparation method thereof, which has the following advantages over the prior art: 1. The present invention uses layer-by-layer self-assembly technology to adsorb corrosion inhibitor materials, and utilizes oppositely charged polyelectrolyte solutions to alternately deposit to prepare porous polyetheretherketone nanoparticles loaded with corrosion inhibitors. By changing the type of polyelectrolyte and the number of depositions, polyelectrolyte multilayer films with different properties can be obtained, which can enhance the adhesion of the corrosion inhibitor on the surface of the nanoparticles, increase the loading amount and distribution uniformity of the corrosion inhibitor, and enhance the corrosion inhibition performance and stability. Since the force of the oppositely charged polyelectrolytes is between the van der Waals force and the covalent bond, the corrosion inhibitor molecules encapsulated between the polyelectrolytes are not easy to leak in large quantities, and the corrosion inhibitor can be slowly released; 2. The present invention selects porous polyetheretherketone nanoparticles as modified materials, mixes them into the epoxy resin matrix, mixes them evenly and solidifies them, which can effectively adjust the microstructure of the epoxy resin, inhibit the crack propagation phenomenon caused by internal hole / crack damage under load, and improve the comprehensive performance of the epoxy resin; and its porous surface structure can effectively adsorb corrosion inhibitor molecules, significantly improve the corrosion resistance of the coating, and can release corrosion inhibitor molecules in the micro-damaged area of ​​the coating to slow down the occurrence of corrosion; 3. The nitrogen-doped carbon quantum dots of the present invention have excellent fluorescence properties, good biocompatibility, high chemical inertness, low toxicity, good specific surface area and abundant surface functional groups. Such quantum dots can effectively avoid polluting the oil environment inside the hydraulic cylinder and ensure the normal operation of the equipment. They are potential green and efficient corrosion inhibitor solutions. The nitrogen-containing groups of nitrogen-doped carbon quantum dots have lone pairs of electrons on their surfaces. Compared with oxygen atoms, they have stronger power supply capacity and are more easily physically and chemically adsorbed with metal matrices. They can be used as efficient adsorption-type corrosion inhibitors. In addition, observing the distribution of nitrogen-doped carbon quantum dots in the hydraulic cylinder through the fluorescence properties of quantum dots can further grasp the corrosion / leakage of the hydraulic system, provide significant visual signals when oil leakage occurs, help to promptly detect oil leakage problems in the hydraulic cylinder, and greatly improve the reliability and service life of the hydraulic system. 4. The modified epoxy resin repair coating material of the present invention has excellent mechanical properties and corrosion resistance, and can effectively inhibit the inner diameter corrosion of the cylinder body. The tensile shear strength is 15MPa and the peel strength is 17.2N / cm. When the coating thickness is 300μm, the charge transfer resistance R ct = 1.2 × 10 10 Ω, in the micro-damaged area of ​​the coating, the composite coating loaded with corrosion inhibitor can slowly release the corrosion inhibitor molecules, further slowing down the occurrence of corrosion; 5. The modified epoxy resin coating of the present invention has excellent machinability. While repairing the damaged coating, it can also reduce the friction and wear between the coating and the rubber ring. The dimensional accuracy and surface quality of the inner diameter of the cylinder body can be maintained through machining to meet the service requirements of the cylinder body parts. The repair process is simple and fast, and can effectively repair the damage caused by corrosion, reducing maintenance time and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Schematic diagram of the anti-corrosion mechanism of the modified epoxy resin coating of the present invention; Figure 2 Provide technical solutions for coating repair due to corrosion failure; Figure 3 The left picture shows the image of the hydraulic cylinder head simulation part, and the right picture shows the image of the hydraulic cylinder head simulation part after composite material coating repair; Figure 4 The microphotographs before and after corrosion repair using the coating repair material of the present invention; Figure 5 To prepare the Nyquist plot of 30CrMnSiNi2A material and metal corrosion repair layer in NaCl solution with a mass concentration of 3.5%; Figure 6 The morphology of the substrate and the corrosion repair layer before and after corrosion: a and b are 30CrMnSiNi2A materials, c and d are repair layer materials. DETAILED DESCRIPTION

[0013] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments: Example 1

[0014] A method for preparing a composite coating material for the inner diameter corrosion surface of a hydraulic cylinder, the specific steps are as follows: (1) Weigh a certain amount of epoxy resin material, polyetheretherketone nanoparticles, curing agent, diluent, deionized water, polyethyleneimine solution, sodium polystyrene sulfonate solution, and nitrogen-doped carbon quantum dot corrosion inhibitor solution; (2) Porous polyetheretherketone nanoparticles with a particle size of 150 to 200 nm were mixed with 200 mL of deionized water at a weight ratio of 1:15 to 1:20, kept in a water bath at 80°C, stirred evenly in a magnetic stirrer for 30 minutes, and dispersed in an ultrasonic disperser for 20 minutes after the stirring was completed; (3) Take 50 ml of the prepared nano-polyetheretherketone dispersion and mix it evenly with 5-10 ml of 5 mg / mL polyethyleneimine (PEI) solution, stir it evenly in a magnetic stirrer for 30 min, disperse it in an ultrasonic disperser for 20 min after stirring, and then centrifuge it for 10-20 min. After centrifugation, pour off the upper solution, wash the lower particles with deionized water, and obtain polyetheretherketone nanoparticles coated with PEI: PEEK / PEI; (4) The prepared PEEK / PEI was mixed with 5-10 ml of 5 mg / mL sodium polystyrene sulfonate (PSS) solution, and stirred evenly in a magnetic stirrer for 20 min. After stirring, the mixture was dispersed in an ultrasonic disperser for 20 min, and separated in a centrifuge for 10-20 min. After centrifugation, the upper layer of the solution was discarded, and the lower layer of particles was washed with deionized water to obtain nanoparticles coated with PSS and PEI layer by layer: PEEK / PEI / PSS; (5) The prepared PEEK / PEI / PSS was mixed with 20-40 ml of 1-5 mg / mL nitrogen-doped carbon quantum dots (N-CQDs, commercially available) corrosion inhibitor solution, and stirred evenly in a magnetic stirrer for 20 min. After stirring, the mixture was dispersed in an ultrasonic disperser for 20 min, and separated in a centrifuge for 10-20 min. After centrifugation, the upper layer of the solution was poured out, and the lower layer of particles was washed with deionized water to prepare polyetheretherketone nanoparticles coated with N-CQDs, PSS, and PEI: PEEK / PEI / PSS / N-CQDs; (6) Repeat steps 4 and 5 once respectively, and place the final particles in an oven and dry them at 60-70 °C for 24 h to prepare porous polyetheretherketone nanoparticles loaded with corrosion inhibitor molecules: PEEK / PEI / PSS / N-CQDs / PSS / N-CQDs; (7) Mix epoxy resin and diluent in proportion, with the diluent dosage being 5wt%, and stir under vacuum for 5-10 minutes; (8) Add porous polyetheretherketone nanoparticles loaded with corrosion inhibitor molecules to the diluted epoxy resin paste material. Note that the mass fraction of the modified polyetheretherketone particles should not exceed 5% of the epoxy resin material. Ultrasonicate the mixed material for 1 h, and then stir it at 65 °C and 280 r / min for 30 min.

[0015] (9) After stirring is completed, add curing agent after the modified material cools down. The volume of curing agent is the same as that of epoxy resin. Stir in vacuum at room temperature for 15 minutes until the coating is evenly mixed. The stirring speed is 280 r / min. The color is brown-red, and the modified epoxy resin coating material is obtained.

[0016] like Figure 2 As shown, the method for repairing the inner diameter corrosion surface of a hydraulic cylinder body using the modified epoxy resin coating material prepared in Example 1 has the following specific steps: (1) Preparation: In this scheme, the base glue is DP420 epoxy resin glue, the repair coating is modified epoxy resin material, and the repair workpiece is the cylinder head with inner diameter corrosion; (2) Cleaning: Use wire cutting to cut open the locally corroded parts of the cylinder head, and use acetone to clean and wipe the surface of the sample; immerse in ethanol for ultrasonic cleaning and repeatedly clean and polish for 10 minutes until the surface corrosion products are removed; grind and polish the cylinder head to meet the requirements that the bottom surface roughness of the placement groove is less than Ra0.8 and the side surface roughness is less than Ra1.6; (3) Preparation of repair coating: modified epoxy resin material is used as the repair coating, which is composed of A / B materials. A material is the epoxy resin part, which contains base resin and other additives. It is the main film-forming material and gives the coating basic properties such as mechanical strength and corrosion resistance. B material is the curing agent part, which reacts with epoxy resin to form a cross-linked network, which plays a role in curing and strengthening the structure. Here, epoxy resin A / B materials are mixed in a volume ratio of 1:1 using an industrial vacuum mixer with a stirring power of 200W and a stirring speed of 280r / min. Stir for 15 minutes until the epoxy resin coating is evenly mixed and the color is brown-red. The repair work is completed within 5 minutes after the coating is exposed to air. (4) Adhesive repair: Apply adhesive to the damaged part of the cylinder head inner diameter. Apply the adhesive evenly to ensure that it is fully infiltrated with the repaired surface. Apply the modified epoxy resin material to the damaged part to be repaired. Use a plastic scraper to apply it on the undried adhesive surface. Apply the epoxy resin repair coating on the inner diameter surface of the cylinder head. The coating surface should be evenly and tightly applied, and the surface should be flat without obvious texture marks. When applying the epoxy resin repair coating, a certain processing allowance should be reserved so that its thickness and shape are slightly larger than the repair area to facilitate subsequent processing. (5) Heating and curing: The repaired part is placed in an autoclave and cured according to the corresponding curing process of the adhesive and curing agent. It is heated to 70°C for curing for 5 hours and placed at room temperature for 24 hours for secondary curing. The second stage is cured at 120°C for 2 hours. In the first stage, the curing is gentle to reduce thermal stress and thermal expansion. In the second stage, the curing temperature is increased to improve the physical and chemical properties and repair quality of the cured repair layer. Here, in order to pursue the best coating repair performance, the coating curing process of heating curing is selected. If the convenience and economy of coating repair are considered, and the repair area and strength requirements are low, curing can be carried out at room temperature. (6) Machining: After the curing process is completed, the repaired part is placed at room temperature for at least 24 hours and then fixed on a lathe for turning. The lathe tool motion parameters are preset using the 3D modeling software: spindle speed 1600 r / min, feed rate 20 m / min, back cutting depth 0.5 mm; remove the excess composite material on the inner surface of the end cover, and grind the cured surface of the excess epoxy resin coating. The minimum radius of the coating after processing should be flush with or slightly larger than the minimum radius of the inner surface of the end cover.

[0017] like Figure 1 As shown in the figure, the modified epoxy resin coating forms a uniform and dense physical barrier to prevent water (H2O), oxygen (O2) and chloride ions (Cl - ) and other corrosive media penetrate into the surface of the metal substrate. This shielding effect reduces the conditions for the occurrence of corrosion reactions and delays the oxidation and corrosion of the substrate. At the same time, the modified polyetheretherketone (PEEK) material added to the coating has the effects of friction reduction, lubrication, anti-corrosion and slow release. When a small amount of corrosive media penetrates the coating and contacts the substrate under the coating, these corrosion inhibitors can play a role in the corrosion site, inhibit the electrochemical reaction, and prevent the further expansion of corrosion.

[0018] like Figure 3 As shown, the surface of the repaired rear end cover is smooth, evenly distributed, and highly dense, which can effectively avoid the contact between the corroded part and the air and reduce stress concentration.

[0019] like Figure 4 As shown in the figure, the microscopic images of the material surface before and after repair. The left picture is the metal surface before repair, where obvious corrosion products and local pits can be observed, and the surface morphology is relatively rough; the right picture is the coating surface after repair, which shows a relatively uniform and delicate surface with no obvious signs of corrosion or color difference.

[0020] After testing, the coating tensile shear strength reached 15MPa; peel strength 17.2N / cm; Figure 5 As shown, when the coating thickness is 0.3 mm, the charge transfer resistance R ct =1.2×10 10Ω, charge transfer resistance R of 30CrMnSiNi2A material ct =1557Ω; Figure 6 As shown in the figure, after the Tafel test, there is no obvious corrosion deterioration on the surface repaired by the epoxy resin coating. Therefore, the coating can effectively protect the actuator end cover from further corrosion and damage and extend the service life of the equipment. The repair scheme can significantly reduce the roughness value of the metal surface and maintain good mechanical properties.

[0021] The above embodiments are only preferred embodiments of the present invention. At the same time, for those skilled in the art, according to the concept of the present invention, there will be changes in the specific implementation methods and application scopes. The contents of the above embodiments should not be understood as limitations on the present invention. Without departing from the principles of the present invention, several improvements and modifications can be made, which should also be regarded as the protection scope of the present invention.

Claims

1. A composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder, characterized in that: The composite coating material is a modified epoxy resin, wherein the modified epoxy resin is epoxy resin uniformly mixed with porous polyetheretherketone nanoparticles, and the surface of the porous polyetheretherketone is coated with corrosion inhibitor layer by layer.

2. The composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 1, characterized in that: The corrosion inhibitor is encapsulated between polyelectrolytes by utilizing the force of polyelectrolytes with opposite charges.

3. The composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 1 or 2, characterized in that: The corrosion inhibitor is nitrogen-doped carbon quantum dots.

4. The composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 1, characterized in that: The main chain structure of the porous polyetheretherketone comprises a ketone bond and two ether bonds.

5. A method for preparing a composite coating material for repairing inner diameter corrosion surfaces of hydraulic cylinder bodies, characterized in that: The following steps are involved: 1) The porous polyetheretherketone nanoparticles and deionized water are uniformly mixed in a weight ratio of 1:15 to 1:20 to obtain a nano-polyetheretherketone dispersion; 2) Evenly mix the nano-polyetheretherketone dispersion with the positively charged polycation electrolyte solution, centrifuge and discard the upper solution, and wash the lower precipitate with deionized water; 3) The precipitate washed in step 2) is uniformly mixed with a negatively charged polyanion electrolyte solution, the upper solution is discarded after centrifugation, and the lower precipitate is washed with deionized water; 4) The precipitate after washing in step 3) is mixed evenly with the nitrogen-doped carbon quantum dots (N-CQDs) corrosion inhibitor solution, the upper solution is discarded after centrifugal separation, and the lower precipitate is washed with deionized water; 5) Repeating the above steps 3) and 4), self-assembling a multilayer film of a positively charged polycation electrolyte and a negatively charged polyanion electrolyte on the surface of the porous polyetheretherketone nanoparticles, and adsorbing a nitrogen-doped carbon quantum dot corrosion inhibitor between the polymer films, the number of repetitions is determined according to demand, and porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitors are obtained; 6) The epoxy resin and porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitor are uniformly mixed under a vacuum environment to obtain a modified epoxy resin composite coating material.

6. The method for preparing a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 5, characterized in that: The positively charged polycation electrolyte is polyethyleneimine.

7. The method for preparing a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 5 or 6, characterized in that: The negatively charged polyanion electrolyte is sodium polystyrene sulfonate.

8. The method for preparing a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 5, characterized in that: The mass of the porous polyetheretherketone is no more than 5% of the epoxy resin.

9. The method for preparing a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 5, characterized in that: Before the epoxy resin is mixed with the porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitor, a diluent is added to the epoxy resin to adjust the viscosity of the epoxy resin.

10. The method for preparing a composite coating material for repairing inner diameter corrosion surface of a hydraulic cylinder body according to claim 5 or 9, characterized in that: The epoxy resin is mixed with porous polyetheretherketone nanoparticles loaded with nitrogen-doped carbon quantum dot corrosion inhibitors, and then a curing agent is added.

Citation Information

Patent Citations

  • Non-toxic corrosion inhibitor and preparation method thereof

    CN112342549A

  • Corrosion-resistant coating material and preparation method thereof

    CN113072853A

  • Friction-modified epoxy resin composite material, preparation method thereof and friction structure

    CN115558243A

  • Nitrogen and sulfur doped carbon quantum dot modified epoxy resin coating as well as preparation method and application thereof

    CN116333556A